Leptin and Iinterlukin-6 relationship and influence of mortality in sepsis - Yi-Hsuan Tsai; Kai-Yin Hung; Wen-Feng Fang (BMC Infectious Diseases)
Abstract Background Sepsis is a severe and life-threatening disease involving multiple risk factors. Leptin has been suggested to play a role in modulating the inflammatory response in sepsis and improving outcomes; however, there are conflicting results regarding the outcome of sepsis. The present study aims to clarify the expression of leptin in patients with sepsis, and its association with other cytokines. Method The retrospective study enrolled 165 adults with sepsis from medical intensive care units (ICU)s, and collected leptin, glucose levels, and cytokines such as IL-6, IL-1RA, IL-10, IL-17, TNF-α, IFN-γfor analysis. Leptin levels were divided into three groups based on concentration: Low (≤ 3.78 ng/mL), Medium (3.78 < leptin ≤ 23.2 ng/mL), and High (> 23.2 ng/mL). Survival curve analysis and comparisons among groups were performed. A subgroup analysis by sex (male and female) was also conducted. Finally, a multiple-factor logistic regression model was used to evaluate the interaction between leptin and other factors. Result The high leptin groups were the oldest (low vs. medium vs. high: 60 vs. 66 vs. 78, p < 0.0001) and had the highest body mass index (BMI) (19.8 vs. 23.9 vs. 24.2, p < 0.0001), the highest percentages of women (28.6 vs. 34.1 vs. 65.9 p = 0.001), and the most comorbidities (1 vs. 1 vs. 2, p = 0.001). After controlling IL-6, day 1 leptin had a trend associated with lower mortality in the hospital (β = 0.984, p = 0.062). The highest IL-6 group had a significantly higher mortality rate among three IL-6 level patients (p = 0.015), but in the high leptin subgroup analysis, the significant effect of high IL-6 on mortality disappeared. Besides, the subgroup analysis of men, the high leptin group had a trend of better survival than the medium and low leptin groups. Conclusion High leptin levels may mitigate the adverse prognostic impact of elevated IL-6 on septic mortality. At comparable IL-6 levels, leptin could serve as a predictor of septic outcomes. Leptin might act as a protective factor in men. Future research should explore leptin’s role in IL-6-mediated inflammation and its potential protective effect in high IL-6 sepsis cases.